Electronic Commerce Projects Adoption and Evaluation in Australian SMEs: Preliminary Findings - Lin, Chad; Cripps, H.; Bode, S. (Publishing House ?Moderna organizacija?, 2005)
IT investments in electronic commerce (e-commerce) are used by organizations, as part of their business strategies, to assist in the inter-organizational acquisition of goods into the value chain and to provide interfaces between customers, vendors, suppliers and sellers. Careful evaluation and adoption of e-commerce projects can assist SMEs in achieving their goals. The results of this research showed that most Australian SMEs interviewed appeared to fail in some ways to conduct a proper assessment of business needs before adopting IT investment in e-commerce. Less than one-third of the Australian SMEs interviewed had carried out some sort of evaluation processes. Most users within these SMEs were not involved in the initial phases of adopting and implementing ecommerce projects and the use of these systems was generally forced upon the them by the senior management. Moreover, the e-commerce systems adopted by the Australian SMEs were not integrated well with other systems. Furthermore, there appeared to be a lack of obvious linkage between the expected outcomes of the e-commerce projects adoption and organizational goals.